Prostate cancer‐specific mortality burden by risk group among men with localized disease: Implications for research and clinical trial priorities. Issue 13 (13th July 2020) - Dee, Edward Christopher; Nezolosky, Michelle D.; Chipidza, Fallon E.; Arega, Melaku A.; Butler, Santino S.; Sha, Sybil T.; Mahal, Brandon A.; Nguyen, Paul L.; Yang, David D.; Muralidhar, Vinayak
Abstract: Objective: To estimate contemporary population‐based patterns of the relative burden of prostate cancer‐specific mortality (PCSM) attributable to each N0M0 prostate cancer risk‐group, that may guide prioritization in research, trial design, and clinical practice. Methods: We categorized 2004‐2015 Surveillance, Epidemiology, and End Results database patients by risk group (low, favorable intermediate, unfavorable intermediate, high, and very highrisk). Using the Fine‐Gray method, we calculated the relative burden of 10‐year PCSM attributable to each risk group. Results: Among N  = 337 162 men (6.8‐year median follow‐up; median age 65 years), the relative proportion of low‐, favorable intermediate‐, unfavorable intermediate‐, high‐, and very high‐risk diagnoses were 29.9% ( N  = 100 969), 31.1% ( N  = 104 696), 17.9% ( N  = 60 360), 18.1% ( N  = 61 023), and 3.0% ( N  = 10 114). Within 10 years of diagnosis, among patients who died of prostate cancer ( N  = 15 064), 5.0% ( N  = 746) had low‐risk, 13.7% ( N  = 2060) had favorable intermediate‐risk, 16.1% ( N  = 2429) had unfavorable intermediate‐risk, 47.8% ( N  = 7196) had high‐risk, and 17.5% ( N  = 2633) had very high‐risk disease at diagnosis. Patients aged 65 and older accounted for 51.9% of all diagnoses and 72.3% of 10‐year PCSM. Although black patients accounted for 15.0% of low‐risk diagnoses, they accounted for 20.6% of 10‐year PCSM. White patients accounted for 80.3% of low‐risk diagnoses and 75.7% of 10‐year PCSM. Conclusion: Although high‐risk and very high‐risk disease account for one‐fifth of diagnoses, they account for two‐thirds of 10‐year PCSM. Older patients and black patients with low‐risk disease accounted for a disproportionately large proportion of deaths. These findings support targeting research toward high‐risk disease and ensuring adequate representation of older and black men in clinical trials.